2008
DOI: 10.1002/pd.2126
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of platelet size changes in gestation and predictive power of elevated MPV in development of pre‐eclampsia

Abstract: Our study provides evidence that MPV gradually increases in pregnant women affected by pre-eclampsia compared to women with normal pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
107
1
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(128 citation statements)
references
References 25 publications
8
107
1
6
Order By: Relevance
“…Despite previous studies showing an association between hematological parameters and PE, the relationship between the severity of hypertension and hematologic parameters in preeclamptic women has not been thoroughly studied (7,8) . This study was undertaken to investigate the relationship between the severity of hypertension (HT) and hematologic parameters in preeclamptic women that can be measured by a simple complete blood count.…”
Section: Introductionmentioning
confidence: 99%
“…Despite previous studies showing an association between hematological parameters and PE, the relationship between the severity of hypertension and hematologic parameters in preeclamptic women has not been thoroughly studied (7,8) . This study was undertaken to investigate the relationship between the severity of hypertension (HT) and hematologic parameters in preeclamptic women that can be measured by a simple complete blood count.…”
Section: Introductionmentioning
confidence: 99%
“…Although MPV should be measured by clinical hematology analysts using sodium citrate, MPV is usually measured as a component of a complete blood count within ethylenediaminetetraacetic acid (EDTA) tubes in routine clinical practice. Since the anticoagulant EDTA induces the platelet shape to change, MPV increases in a time-dependent manner, and the measurements become relatively unreliable [22]. Additionally, one of the other major most important limitations of the study is the difficulty to rule out endometriosis which was the leading cause of secondary dysmenorrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers found no change in the values of these indices between patients and controls (Ceyhan, 2006, Freitas, 2013. Whereas others demonstrated difference in platelet index values (Yong, 2014;Dundar, 2008). This consistency of those studies may be due to the varying methods of platelet indices determination (Ceyhan, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The validity of alteration in the MPV in predicting preeclampsia has been extensively analyzed (Dundar et al, 2008). Many studies concluded that pregnant women with medical disorders with > MPV had an increased risk for developing pre-eclampsia (Jarmo et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation